Effect of fermentation on the constituents in the branches and leaves of Taxus media and non-small cell lung cancer - Guo, Xing; Wang, Rui-Sheng; Zhang, Zhen-Ling; Zhang, Hong-Wei; Wang, Sheng-Chao; Zhang, Shuai; Wu, Ya-Ning; Li, Ya-Jing; Yuan, Jun (Frontiers in Pharmacology, 2024)
Introduction: Non-small cell lung cancer (NSCLC) is a prominent lung cancer disease worldwide. Currently, commonly used methods, such as surgery and radiotherapy, have significant side effects. Traditional Chinese medicine (TCM) has become a research hotspot because of its safe and effective characteristics. The branches and leaves of Taxus media are abundant in antitumor active compounds, and there has been no research conducted as yet regarding its anti-lung cancer molecular mechanism.The aim of this study is to investigate the antitumor activity of two samples before and after fermentation of Taxus media, and to research the molecular mechanism of its inhibitory effect on NSCLC.The chemical composition of pre-fermentation Taxus media (TM) and post-fermentation Taxus media qu (TMQ) were investigated using UHPLC-Q-Qrbitrap HRMS and HPLC. The anti-lung cancer activities of TM and TMQ were compared using an A549-induced tumor mouse model. An ELISA, H&E staining, immunohistochemistry, and immunofluorescence were used to determine the of TMQ mechanism of action.The results indicated that TM and TMQ contained 83 compounds, consisting primarily of flavonoids, organic acids, and taxanes. Both taxanes and flavonoids in TMQ were higher than that in TM. Both TM and TMQ effectively inhibited the tumor growth in NSCLC, and the inhibition rate was greater in TMQ (57.24%) than in TM (49.62%). TMQ administration downregulated the tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and the glutathione (GSH) level and upregulated interferon-γ (IFN-γ), reactive oxygen species (ROS), and malondialdehyde (MDA) levels in the serum of tumor mice. TMQ treatment also increased the protein expression of Bax, Caspase-3, and Beclin-1 in tumor tissues. In contrast, the bcl-2, PI3K, Ki67, ULK1, and mTOR protein levels were suppressed by TMQ. Protein assay analyses reemphasized the superior antitumor effect of TMQ over TM. These cumulative findings demonstrated that the mechanism of action of TMQ was closely related to the activation of transcriptional misregulation in the cancer pathway that inhibited the cholinergic synaptic, AMPK, and PI3K/Akt/mTOR signaling pathways.This study demonstrated that fermentation increased the active ingredient contents and antitumor effects of Taxus media. In addition, post-fermentation TMQ was superior to TM as a herbal medicine for NSCLC treatment.